Dose-Dependent Effects on Sphingoid Bases and Cytokines in Chickens Fed Diets Prepared with Fusarium Verticillioides Culture Material Containing Fumonisins - Bertrand Grenier; Heidi E. Schwartz-Zimmermann; Sylvia Caha; Wulf Dieter Moll; Gerd Schatzmayr; Todd J. Applegate (Toxins, 2015)
In chickens, the effect of mycotoxins, especially fumonisins (FB), in the gastrointestinal tract (GIT) is not well documented. Thus, this study in broiler chicks determined the effects of consuming diets prepared with Fusarium verticillioides culture material containing FB on intestinal gene expression and on the sphinganine (Sa)/sphingosine (So) ratio (Sa/So; a biomarker of FB effect due to disruption of sphingolipid metabolism). Male broilers were assigned to 6 diets (6 cages/diet; 6 birds/cage) from hatch to 20 days containing 0.4, 5.6, 11.3, 17.5, 47.8, or 104.8 mg FB/kg diet. Exposure to FB altered the Sa/So ratio in all tissues analyzed, albeit to varying extents. Linear dose-responses were observed in the kidney, jejunum and cecum. The liver and the ileum were very sensitive and data fit a cubic and quadratic polynomial model, respectively. Gene expression in the small intestine revealed low but significant upregulations of cytokines involved in the pro-inflammatory, Th1/Th17 and Treg responses, especially at 10 days of age. Interestingly, the cecal tonsils exhibited a biphasic response. Unlike the sphingolipid analysis, the effects seen on gene expression were not dose dependent, even showing more effects when birds were exposed to 11.3 mg FB/kg. In conclusion, this is the first report on the disruption of the sphingolipid metabolism by FB in the GIT of poultry. Further studies are needed to reach conclusions on the biological meaning of the immunomodulation observed in the GIT, but the susceptibility of chickens to intestinal pathogens when exposed to FB, at doses lower than those that would cause overt clinical symptoms, should be addressed.